Cerebral Arteriopathies, Venous Thrombosis, and Migraine - Camargo, Erica C. S.; Singhal, Aneesh B. (Seminars in Neurology, 2017)
In this article, the authors review stroke preventive strategies in a diverse group of conditions, namely the nonatherosclerotic cerebral arteriopathies, migraine-associated or migraine-induced stroke, and cerebral venous sinus thrombosis. Although these conditions are less common causes of stroke in the aggregate, they are frequent causes of stroke in teenagers and young adults. Aside from posing unique diagnostic challenges, their management is limited by the absence of randomized clinical trials or high-level evidence that is specific to these conditions. Therapeutic decision-making is largely based on expert opinion, clinical experience, and retrospective studies; it is often empiric. It remains uncertain whether otherwise routine secondary stroke-preventive strategies, such as long-term antiplatelet treatment, lipid-lowering medications, and antihypertensive agents, are applicable to patients with stroke from a cerebral arteriopathy or migraine-associated stroke.
Keywords: ischemic stroke; migraine; cerebral arteritis; cerebral venous thrombosis; stroke prevention